Diversity Problems in Students' Educational Backgrounds and Learning Program Policies of Arabic Language Education - Asse, Ahmad; Putri, Fani Fadhila; Fatimah, Titin; Nursyam, Nursyam; Faqihuddin, Didin (Pascasarjana Universitas KH. Abdul Chalim, 2023)
The aim of this article is to analyze the problems of diversity in students' educational backgrounds and the policies of the UIN Datokarama Palu Arabic Language Education (PBA) learning program. The type of research used in this research is qualitative field research. Meanwhile, the data analysis technique uses the Huberman and Miles method. The results of the research show that the Arabic language learning problems faced by students of the Arabic Language Study Program (PBA) at UIN Datokarama Palu consist of language proficiency problems, psychological problems, and intellectual problems. The Arabic language study program policy is to manage these problems through the application of various learning methods and models, the provision of scholarships, and the formation of Arabic study groups. Through the application of various learning methods and models, language proficiency problems faced by students can be overcome. Meanwhile, providing scholarships is effective in overcoming the psychological problems faced by students. The formation of an Arabic study group is effective in overcoming language proficiency problems and intellectual problems.